Analytical chemistry : Plenary lectures presented at the Fourth Polish Conference on Analytical Chemistry held in Warsaw, Poland during 26-31 Aug. 1974 - Hulanicki, A. (Adam) (Butterworths, 1975)
Analytical Chemistry provides information pertinent to the fundamental aspects of analytical chemistry. This book discusses the development and methods in the field of air and water pollution control monitoring. Organized into 14 chapters, this book begins with an overview of the quantitative and qualitative analysis for other analytical problems. This text then presents the elemental analysis of organic compounds of several elements. Other chapters consider activation analysis, which is the first method to allow the detection and accurate estimation of many trace elements in the human body. T.